Fostering growth: the power of staff acceptance in shaping strategic planning within organizations / Norfashiha Hashim ... [et al.] - Hashim, Norfashiha; Abdul Rahim, Hasyimah; Saad, Nor Hayati; Yahya, Mohamad Faizul; Abdul Haiyee, Zaibunnisa; Kamarulzaman, Mohd Ridwan; Mohamad Taib, Mohamad Fariz; Mohd Yunus, Alwi; Ahmad, Mohamad Ali; Abdul Aris, Nooraslinda; Saipuddin, Siti Fatimah; Ruslan, Mohd Sufian (2023)
In the ever-evolving landscape of modern organizations, the symbiotic relationship between staff acceptance and strategic planning has emerged as a critical driver of growth and success. Staff acceptance is more than just compliance; it embodies the willingness of employees to embrace and actively support the organizational objectives laid out in strategic plans. When employees genuinely believe in the direction and goals of the organization, they become invested stakeholders, contributing their expertise and commitment to the execution of strategic initiatives. This article explores how a culture of open communication and shared purpose enhances staff acceptance. It discusses how organizations that prioritize transparency, provide avenues for employee input, and cultivate a sense of ownership are better positioned to align staff attitudes with strategic goals. Such alignment not only fuels innovation but also strengthens the execution of plans, as employees are more likely to proactively adapt to changes and overcome challenges.